The method of Christian theology : a basic introduction - Putman, Rhyne R. (B & H Publishing Group, 2021)
When handling the things of God, our method matters. Everyone who thinks about God has a method for approaching the subject, whether they recognize it or not. A theological method addresses foundational questions such as: What is theology? How should we approach Scripture? What is the role of tradition, philosophy, and experience? How do we use theology in ministering to others? These questions are vital for anyone studying God and his Word--how one defines theology, sees its task, and uses its sources will shape one's doctrine, for better or worse. In The Method of Christian Theology, Rhyne Putman guides readers through the essential "first words" of systematic theology. Written for entry-level theology students, this book provides clear guidance for using theological sources, reasoning through difficult questions, and applying theological reflection in paper writing and preaching. By studying the foundations of theology, readers will be better equipped to serve God's people in whatever ministry they are called to.